Negotiating Religious Coexistence in a Multi-religious Community: The Genealogical, Cultural and Institutional Dimensions of Tolerance in Cigugur, West Java - Deni Miharja; Andini Andini; Kustana Kustana; Doli Witro; Nurul Alamin; Mohamad Dindin Hamam Sidik; Ayendha Pangesti (Graduate School of UIN Syarif Hidayatullah Jakarta, 2026)
Religious coexistence within multireligious societies is a key issue in the study of religion and pluralism, particularly amidst rising identity polarisation and religion-based conflicts. Although a number of studies have examined tolerance and interfaith harmony in Cigugur, West Java, most have focused on the role of local culture and have not comprehensively explained how religious coexistence is constructed, maintained and reproduced in the social life of the community. This study aims to analyse the social mechanisms that shape and sustain religious coexistence within a multi-religious community in Cigugur, Kuningan Regency, West Java. The research employs a qualitative approach using a case study design. Data were collected through participatory observation, in-depth interviews with religious leaders, community leaders, educators, village officials and local residents, as well as documentation of various social and religious activities within the community. The findings indicate that religious coexistence in Cigugur is constructed through the interaction of three main dimensions: genealogical, cultural and institutional. The genealogical dimension is reflected in inter-religious kinship ties that strengthen social cohesion. The cultural dimension is rooted in collective memory and values passed down through the Sunda Wiwitan tradition. Meanwhile, the institutional dimension is realised through the roles of families, schools, religious leaders, the village administration, and the Forum for Interfaith Harmony in reproducing the values of tolerance and communal living. These three dimensions are maintained through mechanisms of social negotiation that enable the community to manage differences whilst sustaining harmony. This study offers a multidimensional model of religious coexistence that broadens our understanding of interfaith relations within a multireligious society.